THE IMAGE OF WOMEN AND SOCIETY’S ATTITUDES IN ABDULLA QAHHOR’S PROSE: A SOCIO-ECONOMIC ANALYSIS BASED ON SINCHALAK AND MAYIZ YEMAGAN XOTIN - Mavlanova Aziza Isomiddin qizi (TADQIQOTLAR, 2026)
Annotation: This article examines the image of women and the evolution of society’s attitudes toward them in the prose of Abdulla Qahhor, focusing on two contrasting female characters: the secluded wife in the short story “Mayiz Yemagan Xotin” (“The Wife Who Did Not Eat Raisins”) and the young factory worker Saodat in the novella “Sinchalak.” While the first character is confined to the domestic sphere and evaluated solely on the basis of outward piety and conformity, the second enters the productive economy and is evaluated on the basis of competence, vigilance and integrity. The article argues that these two images correspond to two distinct stages in the socio-economic position of women — exclusion from, and inclusion in, public economic life — and interprets the social tension surrounding each character through concepts familiar from economics and social science, including human capital, social capital, information asymmetry and informal institutions. The analysis suggests that Qahhor’s depiction of women’s social position retains direct relevance to contemporary discussions of female labor-force participation and gender norms in Uzbekistan.